10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Despite curative hepatitis C virus (HCV) treatments, only one-third of cases receive treatment nationally. To evaluate how demographic and clinical characteristics were associated with HCV test result awareness and treatment completion, we analyzed programmatic data of a linkage-to-care program in Los Angeles County. Among 512 respondents, 433 (85%) were aware of their positive test result; of those, 138 (32%) received treatment. Black or African American people were less likely (adjusted prevalence odds ratio [APOR] = 0.43; 95% CI, 0.20-0.92) to be aware of their positive test result than White people. Among those aware of their test results, treatment completion was more likely when a specialist physician ordered the HCV test (APOR = 2.13; 95% CI, 1.03-4.41) than when a primary care provider ordered it, and people with symptoms of liver disease were less likely to complete treatment (APOR = 0.16; 95% CI, 0.08-0.35) than people without symptoms. Clinical and community notification and linkage programs, with a focus on racial and ethnic minority populations, will be necessary to bridge the gap between awareness and treatment initiation among Los Angeles County residents.